Perspectives of parents of working adolescents in Ontario, Canada - Viswanathan Shankar; Carol W. Runyan; Scott B. Harpin; John Lewko (BMC, 2021)
Abstract Background More than half of adolescents have jobs in summer or sometime during the year. While employers are ultimately responsible for their safety, parents are often important in helping their children navigate the work environment. Our study examines the attitudes, beliefs and types of involvement parents have in their children's work. Methods We modeled a telephone survey of 507 English-speaking parents of working adolescents in Ontario, Canada on a US study and examined their perspectives, comparing to earlier findings from the U.S. parents. Results Most Ontario parents helped their teens consider questions to ask about work, for example, work hours (90.7%) and job tasks (78.2%) and fewer about workplace safety (57.9%). Parents overall were concerned about their teens, especially younger teens, getting behind on schoolwork (69.3%), being rushed on the job (60.1%) and doing hazardous tasks (58.3%) or working alone (51.9%), or being at work during a robbery (74.5%). Parents of 14-17-year-old daughters were more concerned about their child being assaulted than were parents of sons (62.4% vs. 51.4%), particularly if the teen was in the 18-19 age group (74.3% vs. 52.5%). Half the parents indicated 10-19 h per week was the right amount of work time for their teen, and most agreed that laws should limit the number of hours of youth work. Conclusions Overall, Ontario parents appear to be more concerned about the safety and also more involved in the work of their adolescent children than U.S. parents previously surveyed. Parents are engaged with their children about their work and may serve as valuable assets to helping to advocate for safe work policies and environments.